Corrosion failure assessment on AISI 310s steel used as support of refractory concrete panels in a clinker cooler (2016)
This article presents the corrosion failure assessment on AISI 310 Steel, used as support of refractory concrete panels in a Clinker cooler under a combination of high temperatures and atmospheres with high concentration of sulfur and carbon. It was performed a microstructural analysis by scanning electron microscope with energy-dispersive X-Ray Spectrometer and by optic microscopy techniques. Furthermore it was used Raman spectroscopy in order to determinate the compounds formed in the rust layers. To understand the proposed corrosion mechanism, a thermodynamic simulation was performed on the basis of the 310S steel alloy main elements and temperatures between 700 and 1100 °C in an atmosphere mostly compound by sulfur and low oxygen. The results demonstrate that the material degradation occurred due to a combined process of carburation and sulfidication. As a result of these processes, on one side, it was the impoverishment of chrome in some areas due to the formation of carbides, on the other side, some nickel sulphides compunds emerge as eutectic compounds (Ni-N3S2) with melting points lower than 800 °C, which under this conditions, produce losses of material at the expense of their mechanical properties.